The relationship between health literacy and self-efficacy physical activity in postpartum women - Nooshin Peyman; Monireh Abdollahi (Mashhad University of Medical Sciences, 2016)
Background and objective: Health literacy is the capacity of individuals to obtain process and understand basic health information and services needed to make healthy decisions. Self-efficacy is a predictor for health behaviors such as physical activity. The aim of study was to determine the relationship between health literacy and self-efficacy especially in postpartum women who are at risk of sedentary life. Methods: In this cross-sectional descriptive-analytical study, 120 mothers with children less than three months of age have 20-35 years were selected randomly from all health centers in Mashhad. The instruments used standard questionnaires. Data were analyzed using SPSS and Independent t-test, one-way ANOVA and Pearson Correlation. Results: More than seventy percent of the participants was low (inadequate, boarder line). Significant relationships were found between health literacy and self-efficacy with age (P <0.001), education levels (P <0.001) and breast feeding (P <0.001). Women with adequate health literacy had significantly higher self-efficacy (P <0.001). Conclusion: To improve management weight postpartum and result it, should be developed strategies for promoting health literacy and consequently self-efficacy and physical activity. Paper Type: Research Article.